The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/jedt-01-2019-0028
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the adoption of green certification of buildings

Abstract: Purpose This paper aims to identify the key barriers to the adoption of green certification of buildings in Ghana. Design/methodology/approach The study adopts face-to-face and telephonic interviews with ten built environment professionals, using a semi-structured interview guide. Qualitative responses to the interview were thematically analysed using NVivo 11 Pro analysis application software. Findings The findings suggest that “lack of information on existing green buildings”, “lack of incentives”, “cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 63 publications
0
39
0
Order By: Relevance
“…The sample size for this study was eight (8), made up of two (2) elected people from each stakeholder group. The sample size of eight (8) was considered to be adequate because research has shown that for a qualitative study where researchers seek to obtain rich data through interviews, 2-10 participants are recommended (Agyekum et al, 2019;Parse, 1990). The purposive sampling approach was recommended to each stakeholder group to enable them to select their representatives for the study.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size for this study was eight (8), made up of two (2) elected people from each stakeholder group. The sample size of eight (8) was considered to be adequate because research has shown that for a qualitative study where researchers seek to obtain rich data through interviews, 2-10 participants are recommended (Agyekum et al, 2019;Parse, 1990). The purposive sampling approach was recommended to each stakeholder group to enable them to select their representatives for the study.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple scholars report lack of client awareness and, in turn, lack of demand as barriers to the implementation of eco-design in the building sector [22][23][24][25]. Agyekum et al (2019) argue that when the clients are unaware of the possibilities for eco-designing buildings, or the potential benefits from this, it is difficult for them to show an interest in the subject and thereby also create a market demand [21]. In contrast, some scholars argue that it is a question of perception from the designers, as they perceive clients as uninterested and thereby not convinced that there is a real demand for eco-design [18,26].…”
Section: Barriers Related To Clientsmentioning
confidence: 99%
“…Several scholars identify lack of suitable policies, codes and legislation as one of the main barriers to implementing eco-design in the building sector [18,21,24,27,28], some of which even state that adopting environmental strategies is in conflict with the current regulations [22,29]. Furthermore, existing environmental laws do not necessarily include what is needed for effective implementation [27].…”
Section: Barriers Related To Government/policy-makersmentioning
confidence: 99%
See 2 more Smart Citations